Design-Based Learning as a Pedagogical Approach in an Online Learning Environment for Science Undergraduate Students - Azizan, Suzana Ariff; Abu Shamsi, Nurulaini (Frontiers in Education, 2022)
Design-based learning (DBL) is a learning strategy that requires students to use their theoretical knowledge to develop an artefact or system to tackle a real-life problem. DBL has long been utilized in design-related curricula in higher education such as engineering, computer science, and architecture. However, little is known about how DBL in non-design-based courses enhances students’ learning experience, especially in recent years when the COVID-19 pandemic has compelled the worldwide education systems to adapt to online learning. Hence, this study aims to investigate the experience of science undergraduate students after one semester of participating in online DBL. The participants include 25 second-year science undergraduate students enrolling in the Managing New Technologies course. Using semi-structured interviews, the findings of this study indicated that online DBL contributes to easy access to learning, enhances creativity, and allows students to think outside the box. Nevertheless, students highlighted online learning as an obstacle to their DBL experience. They claimed that online platforms as a means of communication are not practical due to insufficient interaction time and misunderstanding of information. In addition, some students stated that the online environment poses difficulties for collaborative learning.